Masalah Praktikum di Kalangan Guru-Guru Pelatih Institut Perguruan Darulaman - Mohamad Fauzi, Hamid (2003)
Practicum is an important aspect in the teacher training programme. The purpose of this study is to identify the problems and their effect on the Postgraduate Teacher Training Course (PTTC) majoring in Information Communication Technology. The trainee teachers and undergone practicum in four schools in Northern Kedah. Six trainees teachers and four lecturers were selected to be the respondents in this study. The data for this qualitative study were based on interview transcripts, daily lesson plans, reflections by the trainees and observations by the researcher. The problems faced by the trainees with their students could be categorised into teaching and learning problems, discipline problems and class management problems. The problems faced by the trainees with their lecturers were problem concerning evaluation, expectations and comments by the lecturers. All the problems faced by these Postgraduate Teacher Training Course (PTTC) a considerable amount of pressure in them. From the study carried out, the researcher wishes to draw the attention of readers towards the good and the bad experiences faced by these trainee teachers during the practicum. Besides, it is also hoped that the intention of the Teacher Education Division to produce quality teacher be achieved.